EFFECT OF WORKING CAPITAL TURNOVER AND TURNover INVENTORY ON PROFITABILITY AT PT. SIANTAR TOP, Tbk - Thaha, Salmiyah; Arnida, Arnida; Meda, Tamrin (Jurnal Edueco, 2023)
Effect of working capital turnover and inventory turnover on profitability (ROA) at PT. Siantar Top, Tbk. Supervised by Salmiyah Thaha and Jumria. The purpose of this study was to determine the effect of working capital turnover and inventory turnover on profitability (ROA) at PT. SiantarTop, Tbk. The type of data used in this research is qualitative and quantitative data. Source of data used in this research is secondary data. The analytical method used is multiple linear regression analysis, coefficient of determination, correlation coefficient, t test, and F test. The results of this study show the regression equation Y = 11,444 + 0,107X1 + 2,172X2, the coefficient of determination (R2) = 78,20% and correlation coefficient (R) = 0,884. Based on the t test b1 tcount 0,723 < ttable 2,015, b2 tcount 3,748 ttable < 2,015 and through the F test obtained Fcount 8,886 < Ftable 5,790. The results showed that working capital turnover (X1) partially had a positive and insignificant effect on profitability (ROA) while inventory turnover (X2) partially had a positive and not significant effect on profitability (ROA), and simultaneously working capital turnover and turnover Inventory has no significant effect on profitability (ROA) at PT. SiantarTop, Tbk.